Pengaruh Surat Ketetapan Pajak Kurang Bayar, Surat Tagihan Pajak dan Pengusaha Kena Pajak Terhadap Penerimaan Pajak - Lisa Amelia Putri (Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to determine the effect of underpaid tax assessment letters, invoices and entrepreneurs subject to value added tax with notification as a moderating variable. The respondents of this study were 38 employees of KP2KP Dharmasraya. Underpayment tax assessment letters, tax taxes, tax invoices for value added tax receipts with notification, underpaid tax assessment letters, have a positive effect on value added tax receipts with notification as moderating variables at KP2KP Dharmasraya. While the notification letter on the receipt of value added tax, assessment of value added tax tax with a notification letter as a notification of moderating variables of negative influence on KP2KP Dharmasraya